Vulnerability Assessment of Guarani Aquifer Using PESTICIDE-DRASTIC-LU Model: Insights from Brotas Municipality, Brazil - Guerrero, João Vitor; Gomes, Alberto; Lorandi, Reinaldo; Di Lollo, José Augusto [UNESP]; Mataveli, Guilherme; Moschini, Luiz Eduardo (My University, 2024)
Free aquifers have become an important water supply option for underdeveloped and developing countries, due to the resource quality and relatively low extraction prices. However, overexploitation and the lack of territorial planning guidelines in these areas endanger groundwater availability and quality. In this context, this study aimed to analyze the vulnerability to groundwater contamination and contribute to the conservation of the ecosystem services, provided by the Guarani aquifer in Brotas, Brazil, by applying the PESTICIDE-DRASTIC-LU model. The application of this model allowed the identification of priority conservation areas within the context of ecosystem services that groundwater provides to local inhabitants. To this end, we collected, treated, and analyzed seven different hydrogeological data to understand the environmental dynamics of the system and to identify which areas are most vulnerable to aquifer contamination. The results pointed out that 64% of the study area presents zones of high and very high vulnerability to contamination, due to the local hydrogeological characteristics (sandy soils and rocks) and the various anthropogenic activities, mainly with large plantations of sugar cane and eucalyptus. In addition, the mapping allowed the spatial demonstration of the places that should be considered a priority for the conservation of ecosystem services provided by local groundwater. Thus, our results can serve as a baseline to define public action strategies for the preservation and sustainable management of the Guarani aquifer areas.
Keywords: environmental dynamics; GIS; groundwater; guarani aquifer; sustainable management